2017
DOI: 10.24969/hvt.2017.25
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy Induced Cardiovascular Disease

Abstract: Contemporary treatment modalities for malignancy including radiation therapy have led to improved survival. However treatment related complications manifesting later in life including cardiovascular disease has led to survivors exhibiting a lower long term survival rate, when compared to age matched controls. This narrative review will discuss the pathophysiology, risk factors, clinical presentation, management and preventative techniques related to radiotherapyinduced cardiotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Modeling the impact of GCR exposure on the cardiovascular system has proven exceedingly difficult ( Davis et al., 2021 ). Clinical and epidemiologic data obtained from studies of survivors of nuclear accidents, atomic bomb exposure, and radiation-based medical treatments have demonstrated that acute radiation exposure is associated with a higher rate of delayed cardiovascular-related morbidity and mortality ( Ledsome, 2001 ; Taddeo and Armstrong, 2008 ; Baker et al., 2011 ; Adams et al., 2017 ; ; Abdelgawad et al., 2021 ). These studies are limited by confounding factors such as cancer comorbidity, follow-up time post radiation exposure, and estimations of radiation dose.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling the impact of GCR exposure on the cardiovascular system has proven exceedingly difficult ( Davis et al., 2021 ). Clinical and epidemiologic data obtained from studies of survivors of nuclear accidents, atomic bomb exposure, and radiation-based medical treatments have demonstrated that acute radiation exposure is associated with a higher rate of delayed cardiovascular-related morbidity and mortality ( Ledsome, 2001 ; Taddeo and Armstrong, 2008 ; Baker et al., 2011 ; Adams et al., 2017 ; ; Abdelgawad et al., 2021 ). These studies are limited by confounding factors such as cancer comorbidity, follow-up time post radiation exposure, and estimations of radiation dose.…”
Section: Introductionmentioning
confidence: 99%